Pre Calculus

Multiply; then use fundamental identities to simplify the expression below and determine which of the following is not equivalent.
(sin x + cos x) ^2

a. 1+2sinxcosx

b. sec^2x−tan^2x+2cosxsinx

c.sec x + 2 sin x/sec x

d. sin^2x+cos^2x

e. 1+2cos (pi / 2 - x) cos x

asked by Jessica Maths
  1. you know that sin^2 x + cos^2 x = 1, so when you expand you have

    sin^2 x + 2 sinx cosx + cos^2 x

    recall also that sec^2 x = 1 + tan^2 x

    cos(pi/2-x) = sin(x)

    So, what do you think?

    posted by Steve

Respond to this Question

First Name

Your Answer

Similar Questions

  1. Studying for math test

    Multiply; then use fundamental identities to simplify the expression below and determine which of the following is not equivalent. (sin x + cos x) ^2 a. 1+2sinxcosx b. sec^2x−tan^2x+2cosxsinx c. sec x + 2 sin x/sec x d.
  2. Math(Please check)

    Use the fundamental identities to simplify the expression. tan^2 Q / sec^2 Q sin^2/cos^2 / 1/cos^2 = sin^2 / cos^2 times cos^2 / 1 = The cos^2 cancels out so sin^2 is left. Is this correct?
  3. trig 26

    simplify to a constant or trig func. 1. sec ²u-tan ²u/cos ²v+sin ²v change expression to only sines and cosines. then to a basic trig function. 2. sin(theta) - tan(theta)*cos(theta)+ cos(pi/2 - theta) 3. (sec y - tan y)(sec y
  4. Pre Calculus

    Use one of the identities cos(t + 2ðk) = cos t or sin(t + 2ðk) = sin t to evaluate each expression. (Enter your answers in exact form.) (a) sin(17ð/4) (b) sin(−17ð/4) (c) cos(17ð) (d) cos(45ð/4) (e) tan(−3ð/4)
  5. Pre Calculus

    Use one of the identities cos(t + 2ðk) = cos t or sin(t + 2ðk) = sin t to evaluate each expression. (Enter your answers in exact form.) (a) sin(17ð/4) (b) sin(−17ð/4) (c) cos(17ð) (d) cos(45ð/4) (e) tan(−3ð/4)
  6. pre cal

    Use identities to simplify each expression. sin(x)+cos^2(x)/sin(x) = ? tan^3(x)−sec^2(x)tan(x)/cot(−x) = ? sin^4(x)−cos^4(x) =?
  7. Integration

    Intergrate ¡ì sec^3(x) dx could anybody please check this answer. are the steps correct? thanks. = ¡ì sec x d tan x = sec x tan x - ¡ì tan x d sec x = sec x tan x - ¡ì sec x tan^2(x) dx = sec x tan x + ¡ì sec x dx - ¡ì
  8. calculus trigonometric substitution

    ∫ dx/ (x^2+9)^2 dx set x = 3tan u dx = 3 sec^2 u du I = 3 sec^2 u du / ( 9 tan^2 u + 9)^2 = 3 sec^2 u du / ( 81 ( tan^2 u + 1)^2 = sec^2 u du / ( 27 ( sec^2 u )^2 = du / ( 27 sec^2 u = 2 cos^2 u du / 54 = ( 1 + cos 2u) du /
  9. Trigonometry desperate help, clueless girl here

    2. solve cos 2x-3sin x cos 2x=0 for the principal values to two decimal places. 3. solve tan^2 + tan x-1= 0 for the principal values to two decimal places. 4. Prove that tan^2(x) -1 + cos^2(x) = tan^2(x) sin^2 (x). 5.Prove that
  10. trig

    how do you start this equation i've been tryng it for 20min. sec^6x(secxtanx)-sec^4x(secxtanx)=sec^5xtan^3x ec^6x(secxtanx)-sec^4x(secxtanx)=sec^5xtan^3x Factor out a sec^5 tan and divide thru. Left is sec^2 x = Tan^2 x Then this

More Similar Questions